Improving Women's Cardiovasular Health: A Position Statement From the International Council on Women's Health Issues - Davidson, P.; Meleis, A.; McGrath, S.; DiGiacomo, Michelle; Dharmendra, T.; Puzantain, H.; Song, M.; Riegel, B. (Taylor & Francis Group LLC, 2012)
Cardiovascular disease (CVD) is the number one killer of women worldwide, and it remains the primary cause of death and disability in both developed and developing countries. The International Council on Women’s Health Issues is an international nonprofit association dedicated to the goals of promoting the health, health care, and the well-being of women. Based on the outcomes of a facilitated discussion at its 18th biannual meeting, delegates aim to raise awareness about the potent influence of gender-specific factors on the development, progression, and outcomes of CVD. Key recommendations for decreasing the burden of CVD are also discussed.